Diagnostic and Prognostic Value of Hyperammonemia in Patients with Liver Cirrhosis, Hepatic Encephalopathy, and Sarcopenia (Experts’ Agreement) - Nadinskaia, M. Yu; Maevskaya, M. V.; Bakulin, I. G.; Bessonova, E. N.; Bueverov, A. O.; Zharkova, M. S.; Okovityi, S. V.; Ostrovskaya, A. S.; Gulyaeva, K. A.; Ivashkin, V. T. (Rossiĭskiĭ zhurnal gastroėnterologii, gepatologii, koloproktologii, 2024)
Introduction. In cirrhotic patients, hyperammonemia develops due to impaired ammonia detoxification and portosystemic blood shunting and is most commonly associated with hepatic encephalopathy and sarcopenia. Currently, there are questions regarding the diagnosis of hyperammonemia and the effect of ammonia-lowering therapy on disease outcomes. Materials and methods. The Russian Scientific Liver Society selected a panel of seven experts in liver cirrhosis research and management of patients with this disease to make reasoned statements and recommendations on the issue of diagnostic and prognostic value of hyperammonemia in patients with liver cirrhosis, hepatic encephalopathy and sarcopenia. Results. The Delphi panel identified the most relevant topics, in the form of PICO questions (patient or population, intervention, comparison, outcome). The Delphi panel made six questions relevant to clinical practice and gave reasoned answers, framed as ‘clinical practice recommendations and statements’ with evidence-based comments. The questions and statements were based on the search and critical analysis of medical literature by keywords in Englishand Russian-language databases. The formulated questions could be combined into four categories: hepatic encephalopathy, sarcopenia, hyperammonemia, and ammonia-lowering therapy. Conclusions. The results of the experts' work are directly relevant to the quality management of patients with liver cirrhosis, and their recommendations and statements can be used in clinical practice.